Thomas Sharp's Collaboration With H. De C. Hastings: the Formulation of Townscape as Urban Design Pedagogy - Erten, Erdem; Erten, Erdem (Routledge, 2009)
This paper focuses on the collaboration between the Architectural Review's (AR) chief editor and proprietor Hubert de Cronin Hastings (1902-1986) and planner Thomas Sharp (1901-1978) in the formulation and dissemination of Townscape as urban design pedagogy in the period between 1935 and 1955. This pedagogy proved effective in questioning the modernist planning attitude defined by the CIAM congresses and the prevalent Garden City mentality of the New Town proposals during post-World War II reconstruction efforts. Growing out of the shared interests and ideological affinities of the people engaged in British post-war reconstruction, 'Townscape' emerged as the result of a collective effort of those affiliated with Hastings for which Nikolaus Pevsner, Thomas Sharp and Gordon Cullen assumed major roles. If the Architectural Press has been the linchpin of this propagation by several books including those by Sharp and the articles published within AR, Sharp's role as a practicing planning consultant was influential, but more importantly institutional in disseminating 'Townscape'. The intermittent collaboration between Hastings and Sharp was a part of Hastings's unrelenting effort in conceptualizing a model of environmental intervention linked to ideals of cultural continuity. Townscape series remained a part of AR during Hastings's editorial reign for more than a quarter century, repeating the same message for different contextual cases as an instrument of teaching its readers how to perceive, visualize and intervene into the urban environment, as much as Townscape was an inseparable component of Sharp's career as planner, lecturer and author that established precedents for many planners to follow.
Keywords: H. de C. Hastings; Mid-twentieth century urban design; Thomas Sharp; Townscape; Visual planning